Pengaruh Kewajaran Harga dan Pengalaman Pelanggan Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Loyalitas Pelanggan pada Apotek Setia Medika di Jakarta Barat - Setia, Astutik; Bernarto, Innocentius (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research is to examine the influence of pricing fairness and customer experience on customer satisfaction and its subsequent effect on customer loyalty at Setia Medika Pharmacy, West Jakarta. The sampling method used was purposive sampling within a non-probability framework, with a sample size of 200 respondents who were consumers of pharmacies. Data were gathered using a questionnaire aimed at assessing consumer opinions of pricing equity and shopping experience. The used data analysis technique is multiple regression analysis using the Smart-PLS 4 software to examine the interrelationship among variables. The findings indicated that pricing fairness significantly enhances consumer happiness and loyalty. Furthermore, customer experience positively influences customer satisfaction, which significantly affects customer loyalty. These data affirm that enhancing pricing equity and customer experience may lead to more happiness, therefore augmenting customer loyalty in pharmacies. This study offers significant insights for pharmacy management in developing successful marketing strategies to enhance client happiness and loyalty.